Pragmatic Scala create expressive, concise, and scalable applications - Subramaniam, Venkat (Pragmatic Bookshelf, 2015)
Our industry is moving toward functional programming, but your object-oriented experience is still valuable. Scala combines the power of OO and functional programming, and Pragmatic Scala shows you how to work effectively with both. Updated to Scala 2.11, with in-depth coverage of new features such as Akka actors, parallel collections, and tail call optimization, this book will show you how to create stellar applications. The first edition of this book was released as Programming Scala .
Place of publication from publisher's website. - Includes bibliographical references. - Description based on online resource; title from title page (Safari, viewed November 13, 2015)
Keywords: Scala (Computer program language); Scala (Langage de programmation)